Building Stock Portfolio Using Peter Lynch's Investment Strategy in Indonesia Stock Exchange - Owen, Jeremy; Koesrindartoto, Deddy Priatmodjo (Journal of Business and Management, 2020)
Abstract. Peter Lynch is one of the most influential and regarded as legendary investor of wall street. He managed to outperform the S&P500 index 13 years in a row, by doubling the S&P500 performance. It would be great to implement this strategy in Indonesia during several market condition, bearish of 2015-2017, bullish of 2016-2018 and sideways of 2017-2019 for Indonesian investors. This brings the question whether it’s applicable during the 3 markets condition in Indonesia Stock Exchange. This research uses primary data that is gathered mainly through Yahoo Finance and Stockbit.com, where this research could get historical data of the stocks, the Jakarta Composite Index, 10 years government bonds of Indonesia and other necessary data for this research. From this research, the result is, Peter Lynch’s investment strategy performs statistically better during bearish market using equally weighted method of portfolio allocation. However, the bullish and sideways market using equally weighted method is not superior compared to the market. Same goes with bearish, bullish and sideways market using market capitalization method. This was confirmed using paired t-test for normally distributed data and Mann-Whitney u-test for data that is not normally distributed. The ratio measures the performance of portfolio and compared it with the benchmark which is the Jakarta Composite Index.Keywords: Peter Lynch, stock, portfolio, Indonesia Stock Exchange